Who can be conservative? - JUNG, Wooyong (KDI School, 2016)
Nowadays in democratic countries, it is not difficult to find a particular voting pattern in which people who are less educated, older, and receive less income tend to vote conservative parties. South Korea is no exception where the political preference among different groups defined by income, age, education level has been clearly divided. This study tried to find the logic behind the voting pattern in Korea by delving into the formation process of political orientation. To this end, it revisited Veblen’s theory, according to which only two groups of individuals can keep their conservativeness either willingly or passively: one group which has enough wealth to stand against the pressure of change; and the other so destitute that cannot even afford to think of the changeand adaptation. In order to prove this, this study applied the WVS data conducted in Korea since 1990to the theory using several pooled OLS and logit models. As a result, this study showed that the conservativeness decreased as the level of income increased; however, the extent to which the conservative orientation reduced became smaller. It meant that the upper crust and the bottom of a society showed more conservative inclination than other groups of people. Also it was proved that the cohort effect clearly exists in the formation of political orientation. That is, individuals are largely influenced by theirown growth environment when the political orientation was established.
Thesis(Master) --KDI School:Master of Development Policy,2016